2018
DOI: 10.1186/s12891-018-2030-x
|View full text |Cite
|
Sign up to set email alerts
|

Developing a risk prediction model for the functional outcome after hip arthroscopy

Abstract: BackgroundHip arthroscopic treatment is not equally beneficial for every patient undergoing this procedure. Therefore, the purpose of this study was to develop a clinical prediction model for functional outcome after surgery based on preoperative factors.MethodsProspective data was collected on a cohort of 205 patients having undergone hip arthroscopy between 2011 and 2015. Demographic and clinical variables and patient reported outcome (PRO) scores were collected, and considered as potential predictors. Succe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…A strong body of literature has demonstrated the interaction of mental health on perception of pain and function prior to, and following, hip arthroscopy. 3,4,[6][7][8][9][10][11] Less studied is the impact of hip arthroscopy on psychological comorbidities. Following hip arthroscopy for FAIS, Sochacki et al showed that 66.2% of patients had a minimal, clinically important difference in reduction scores from preoperative to 1 year postoperative on the Beck Depression Inventory-II.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A strong body of literature has demonstrated the interaction of mental health on perception of pain and function prior to, and following, hip arthroscopy. 3,4,[6][7][8][9][10][11] Less studied is the impact of hip arthroscopy on psychological comorbidities. Following hip arthroscopy for FAIS, Sochacki et al showed that 66.2% of patients had a minimal, clinically important difference in reduction scores from preoperative to 1 year postoperative on the Beck Depression Inventory-II.…”
Section: Discussionmentioning
confidence: 99%
“…5 For patients undergoing hip arthroscopy, poor mental health has been correlated with worse preoperative patient-reported outcomes, 3,4,6 persistent postoperative pain, 7 and decreased postoperative patient reported outcomes (PROs). 4,6,[8][9][10][11] However, it remains unknown whether there is a potential bidirectional relationship between hip pain and poor mental health, as there is a paucity of research devoted to understanding how mental health disorders may be affected by surgical treatment of musculoskeletal conditions. Although not specific to those with preoperative depression or anxiety, Sochacki et al demonstrated 66.2% of patients had minimal clinically important decreases in depressive symptoms following hip arthroscopy for femoral acetabular impingement syndrome (FAIS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This identified several pre-operative risk factors: (1) gender, indication: (2) pincer and (3) labral tear, along with pre-operative PROM scores including measures of psychological health. [54] Without taking into account intra-operative parameters, this model successfully predicted outcome in 71% of cases.…”
Section: Outcome-based Interventionmentioning
confidence: 99%
“…The shift to personalized medicine, which involves decision-making based on the unique characteristics of each specific patient, is the next step in improving results of our treatments. Several recent studies in the field of hip arthroscopy [8,10] have created predictive algorithms and models to predict patient-reported outcomes as well as the risk of hip preservation failure. We recently published a model based on pre and intraoperative findings to predict risk of conversion of an arthroscopic labral repair to a THA [8].…”
Section: How Do We Get There?mentioning
confidence: 99%